2011
DOI: 10.1007/s11160-011-9231-9
|View full text |Cite
|
Sign up to set email alerts
|

Variable B chromosomes frequencies between males and females of two species of pufferfishes (Tetraodontiformes)

Abstract: Cytogenetic analysis in two sympatric species of pufferfish from Paraná Coast, Brazil, Sphoeroides spengleri (Tetraodontidae) and Chilomycterus spinosus (Diodontidae) revealed the presence of 2n = 46 and 2n = 50 chromosomes, respectively. In S. spengleri, the double FISH technique with 5S and 18S rDNA probes showed no syntenical organization, with both multigene families occupying a terminal position on the chromosomes. In S. spengleri the poor pattern of heterochromatin distribution is discussed about its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Microchromosomes were also reported in other fishes and most of these microchromosomes were considered to be supernumerary chromosomes, which were suggested to have an effect on the phenotype of host species, especially the sex (Schartl et al 1995;Noleto et al 2012). In Chilomycterus spinosus (Noleto et al 2012) and one clone of P. formosa (Lamatsch et al 2000;Lamatsch et al 2010), they were revealed to be associated with male determination; whereas in Sphoeroides spengleri, they were found to be related to female determination (Noleto et al 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Microchromosomes were also reported in other fishes and most of these microchromosomes were considered to be supernumerary chromosomes, which were suggested to have an effect on the phenotype of host species, especially the sex (Schartl et al 1995;Noleto et al 2012). In Chilomycterus spinosus (Noleto et al 2012) and one clone of P. formosa (Lamatsch et al 2000;Lamatsch et al 2010), they were revealed to be associated with male determination; whereas in Sphoeroides spengleri, they were found to be related to female determination (Noleto et al 2012).…”
Section: Discussionmentioning
confidence: 93%
“…In Chilomycterus spinosus (Noleto et al 2012) and one clone of P. formosa (Lamatsch et al 2000;Lamatsch et al 2010), they were revealed to be associated with male determination; whereas in Sphoeroides spengleri, they were found to be related to female determination (Noleto et al 2012). Intriguingly, the extra microchromosomes in male gibel carp are dispensable for a normal life cycle, and their number and morphology varies between individuals (Figure 2 and Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…However, some specific situations indicate probable roles performed by these chromosomes, as in the cichlid species from Lake Victoria (Africa), where a female-specific B chromosome carries several genes encoding proteins, highlighting its possible functional effect on female sex determination (Yoshida et al, 2011). Likewise, in Chilomycterus spinosus (Tetraodontiformes), a B chromosome is restricted to males and behaves as a univalent during meiosis, also suggesting its correlation with sex differentiation in this species (Noleto et al, 2012). Similarly, in Astyanax scabripinnis (Characiformes), B chromosomes have a major occurrence among females, besides their altitudinal variation in frequency (Néo et al, 2000a,b), suggesting possible adaptive effects.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulation of satellite DNA in certain chromosomal regions may play a role in modeling the karyotype structure of species, causing both functional (position-effect variegation) and structural changes (fissions, fusions, and inversions), thus contributing to karyotypic diversity in some marine groups, as observed in Tetraodontiformes (Noleto et al 2012) and Perciformes (Affonso and Galetti 2005).…”
Section: Discussionmentioning
confidence: 99%